Marine ecosystem regime shifts induced by climate and overfishing: a review for the Northeern Hemisphere - Möllmann, Christian; Diekmann, Rabea (2012)
Abrupt and rapid shifts in food web and community structure, commonly termed regime shifts, have been increasingly reported for exploited marine ecosystems around the world. Here, we present a review on regime shifts in Northern hemisphere marine ecosystems, most of them using a multivariate approach to statistically analyse time series. We show that rapid shifts occurred in synchrony during the late 1980s/early 1990s, suggesting a common large-scale climate driver and essentially matching times of change in the North Atlantic Oscillation and other atmospheric indices, which modified, for example, the local temperature regimes. We further show that trophic cascades triggered by overfishing and causing a switch of trophic regulation are regularly involved in ecosystem reorganizations. Eutrophication and the introduction of alien species can be important as well, potentially affecting tipping points or the food web structure. Our review highlights how multiple drivers potentially interact in a way that one driver undermines resilience (e.g. overfishing) and the other (e.g. climate change) gives the final impulse for an abrupt change. Further, ecosystem regime shifts can be particularly difficult to reverse when alternative stable states are involved. Understanding the drivers and mechanisms leading to regime shifts is crucial for developing ecosystem-based management strategies and establishing early-warning systems to avoid catastrophic ecosystem changes and achieve a sustainable exploitation of ecosystem services.